Fabrication and mechanical characterization of YAG ceramic-composite with alumina nanoparticles using slip casting and sintering process - M Torki; B Movahedi; S Ghazanfari; M Milani (Materials Research Express, 2020)
The aim of this study was to fabricate a YAG/Al _2 O _3 ceramic composite with different alumina nanoparticles using slip casting and the atmospheric sintering process. In addition, some mechanical properties such as hardness and elastic modules of this ceramic were evaluated using the nanoindention technique. The results showed that the rheological behavior of the slurry was optimized to the solid loading of 55 wt%; also, the relative density of the green body was enhanced up to 65%. Relative density was increased to 99.5% after sintering at 1700 °C for 12 h; further, the pore size (150 nm) was reduced to half of that of powder particles. It should be, however, noted that the optimum amount of alumina nanoparticles as a reinforcing agent in the matrix was less than 5%wt and the composite hardness was increased to 7.3%, as compared to the pure YAG ceramic.